Assessment of labially impacted canines traction mode with clear aligners vs. fixed appliance: A comparative study based on 3D finite element analysis - Xia, Qian; He, Yao; Jia, Lurong; Wang, Chunjuan; Wang, Weixu; Wang, Chao; Song, Jinlin; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: The objective of this study was to evaluate and compare the biomechanical differences between clear aligner and fixed appliance in the traction of labially impacted canines based on 3D finite element analysis, and to assess the discrepancies between diverse traction models of invisible orthodontics. Methods: A series of patient-oriented finite element models were constructed, including a maxillary dentition with a right labially canine, maxilla, periodontal ligaments, traction attachments, and clear aligners. The two most common clinical scenarios were investigated: Scenario A: impacted canine (distal) and Scenario B: impacted canine (mesial). For each clinical scenario, three traction models with clear aligners and one fixed appliance model were established. Results: In all four models, the impacted canines exhibited similar initial displacement tendencies of mesially rotated in Scenario A and distally rotated in Scenario B, and with small differences in periodontal ligament stress magnitude. However, the sum of the periodontal ligament stresses of the anchorage teeth in the clear aligner mode was in the range of 56.28-76.21kPa and in the fixed appliance mode was in the range of 6.61-7.22kPa. The maximum value of initial displacement of the anchorage teeth in the clear aligner mode was in the range of 13.71- 19.72μm, while in the fixed appliance mode was 3.10- 3.92μm. Conclusion: For impacted canines, clear aligner mode and fixed appliance mode have little difference in biomechanical effect. However, the anchorage teeth in the clear aligner mode will endure higher stress and show a more pronounced displacement tendency. In addition, the biomechanical effects of different clear aligner traction models are various but not obvious.